ANTARA KRITIK DAN ANARKI: FRAMING TEMPO.CO DALAM PEMBERITAAN AKSI "INDONESIA GELAP" - Nur Rohman; Moch Zakki; Siti Rodhiah; Adventalia Dela Prasetya; Safira; Husein Abdullah; Ahmadinejad Hilmi; Eko Lutfi; Amar Yazid; Malik Ibrahim (Nusantara Hasana Journal, 2026)
This research is motivated by the “Indonesia Gelap” (Dark Indonesia) student protest movement in February 2025, one of the largest protest events after the inauguration of the new president. Research on media framing of post-election student protest actions remains very limited. This study aims to reveal how Tempo.co framed the “Indonesia Gelap” movement using Erving Goffman’s dramaturgical theory, focusing on the concepts of front stage, back stage, impression management, definition of the situation, audience, and inauthenticity. This qualitative research employs dramaturgical analysis on four Tempo.co news articles published in February 2025. The findings reveal a striking gap between the front stage performance of power actors and back stage realities, failed impression management, and inauthenticity that ultimately reinforces the “Indonesia Gelap” narrative. Tempo.co consistently acts as a media outlet that exposes the back stage of power and sides with the public’s definition of the situation. This study concludes that Tempo.co frames the protest as constructive social criticism rather than anarchy, and confirms the relevance of Goffman’s dramaturgical theory in analyzing media and power dynamics in contemporary Indonesia.